2021
DOI: 10.1186/s13358-021-00242-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Pliensbachian–Toarcian crisis on belemnite assemblages and size distribution

Abstract: The second-order Pliensbachian–Toarcian crisis affected major groups of marine organisms. While its impact has been intensively studied for ammonites, the response of belemnites is only currently emerging through quantitative studies. Novel overall and regional diversity analyses suggest that belemnite richness in the NW-Tethys drops at the Pliensbachian–Toarcian boundary, while overall diversity slightly increases in NW-Tethys assemblages during the Toarcian Oceanic Anoxic event (T-OAE), mostly driven by NW E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Klug et al (2015a) investigated the temporal and spatial controls on Paleozoic marine invertebrate gigantism and could demonstrate relationships with increased diversity as well as environmental factors like oxygenation, temperature and sea level. Increased diversity, disparity or preservation are unlikely to explain this pattern in Bajocian belemnites as the diversity, disparity and preservation of Bajocian belemnites seem eclipsed by the Toarcian (Dera et al, 2016), but further analyses comparable to those in the Lower Jurassic (De Baets et al, 2021;Neige et al, 2021;Rita et al, 2021) are necessary to further corroborate these patterns. Meer et al ( 2022) studied sea-level changes in the Phanerozoic.…”
Section: Was There a Bajocian Marine Animal Gigantism?mentioning
confidence: 97%
See 1 more Smart Citation
“…Klug et al (2015a) investigated the temporal and spatial controls on Paleozoic marine invertebrate gigantism and could demonstrate relationships with increased diversity as well as environmental factors like oxygenation, temperature and sea level. Increased diversity, disparity or preservation are unlikely to explain this pattern in Bajocian belemnites as the diversity, disparity and preservation of Bajocian belemnites seem eclipsed by the Toarcian (Dera et al, 2016), but further analyses comparable to those in the Lower Jurassic (De Baets et al, 2021;Neige et al, 2021;Rita et al, 2021) are necessary to further corroborate these patterns. Meer et al ( 2022) studied sea-level changes in the Phanerozoic.…”
Section: Was There a Bajocian Marine Animal Gigantism?mentioning
confidence: 97%
“…In recent decades, belemnites have gained importance because of their use in isotope geochemistry (e.g., Dera et al, 2009;Hoffmann & Stevens, 2020;Mutterlose et al, 2010;Stevens et al, 2014 and references therein), to study diversity and size changes (De Baets et al, 2021;Neige et al, 2021;Rita et al, 2019) as well as disparity analyses (Dera et al, 2016;Nätscher et al, 2021) across extinction events. Ippolitov et al (2018), Hoffmann andStevens (2020) and Stevens et al (2022) demonstrated how different materials such as calcite, aragonite, and organic components are distributed in the rostrum.…”
Section: Introductionmentioning
confidence: 99%
“…By the Early Jurassic, belemnites had reached a cosmopolitan distribution and relatively high diversity and abundance (e.g., Iba et al, 2014aIba et al, , 2014bWeis et al, 2015a). Although affected by second-order extinction events (e.g., Dera et al, 2016;De Baets et al, 2021;Neige et al, 2021), belemnites continued to be diverse during the Jurassic and early Early Cretaceous (e.g., Schlegelmilch, 1998;Mutterlose, 1988Mutterlose, , 1998Iba et al, 2011), with the two last occurring, disjunctively distributed families, the Boreal Belemnitellidae and the Austral Dimitobeli-dae, finally becoming extinct at the K/Pg-boundary (e.g., Doyle, 1992;Christensen, 1997;Iba et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By the Early Jurassic, belemnites had reached a cosmopolitan distribution and relatively high diversity and abundance (e.g., Iba et al, 2014a, 2014b; Weis et al, 2015a). Although affected by second-order extinction events (e.g., Dera et al, 2016; Neige et al, 2021; De Baets et al, 2021), belemnites continued to be diverse during the Jurassic and early Early Cretaceous (e.g., Schlegelmilch, 1998; Mutterlose, 1988, 1998; Iba et al, 2011), with the two last occurring, disjunctively distributed families, the Boreal Belemnitellidae and the Austral Dimitobelidae, finally becoming extinct at the K/Pg-boundary (e.g., Doyle, 1992; Christensen, 1997; Iba et al, 2011).…”
Section: Introductionmentioning
confidence: 99%